Strengthening PERGUNU's Prophecy Movement through Mentoring at the NU Branch Leadership Level in Pasuruan City - Makhmud, Ikhwan; Bustomi, Abu Amar; Darmayanti, Rani; Vedianty , Adinda Syalsabila Aidha; Amelia, Nahdiyah Dwi; Hujjah, Shochibul (CV. BImbingan Belajar Assyfa, 2024)
The Nahdlatul Ulama Teachers Association (PERGUNU) plays a pivotal role in enhancing education and moral values within society. This study addresses the necessity to strengthen PERGUNU's prophecy movement through a participatory mentoring program at the Nahdlatul Ulama Branch Leadership (PC NU) level in Pasuruan City, slated for August 2024. The goal is to enhance leadership skills and community participation through a structured mentoring process. Employing a mixed-method approach with a sequential explanatory design, the study consists of two phases. The quantitative phase involves a survey of 100 respondents to gather broad perceptions and experiences, while the qualitative phase includes in-depth interviews and focus group discussions with 20 participants for deeper insights. The subjects are active PERGUNU members engaged in PC NU activities, focusing on teachers, leaders, and mentoring program participants. Data collection involves quantitative surveys and qualitative interviews, analyzed using SPSS software and thematic analysis, respectively. Reliability and validity are ensured through data triangulation and peer review. Preliminary findings suggest participatory mentoring significantly boosts teacher morale, pedagogical competence, and community engagement. The study recommends expanding the program regionally, ensuring sustainability, and integrating feedback for continuous improvement, contributing significantly to educational leadership and community empowerment in Islamic education.